Grande sonate pathétique, op. 13 / L.v. Beethoven ; revidirt und mit Fingersatz versehen von K. Klauser - Beethoven, Ludwig van, 1770-1827 (composer):::::::::::::::; Klauser, Klaus (editor):::Contributor:::::::::::: (Hamburg; Germany; Schuberth & Co., 2022)
Mid-nineteenth century edition of the Piano Sonata no. 8 in C minor, op. 13, published by Schuberth & Co. as part of the "Neue wohlfeile Prachtausgabe" edited by Karl Klauser.